Genetics of age‐related hearing loss. Issue 9 (27th January 2020) - Wells, Helena Rose Rees; Newman, Tracey A.; Williams, Frances M. K.
Abstract: Age‐related hearing loss (ARHL) has recently been confirmed as a common complex trait, that is, it is heritable with many genetic variants each contributing a small amount of risk, as well as environmental determinants. Historically, attempts to identify the genetic variants underlying the ARHL have been of limited success, relying on the selection of candidate genes based on the limited knowledge of the pathophysiology of the condition, and linkage studies in samples comprising related individuals. More recently genome‐wide association studies have been performed, but these require very large samples having consistent and reliable phenotyping for hearing loss (HL), and early attempts suffered from lack of reliable replication of their findings. Replicated variants shown associated with ARHL include those lying in genes GRM7, ISG20, TRIOBP, ILDR1, and EYA4. The availability of large biobanks and the development of collaborative consortia have led to a breakthrough over the last couple of years, and many new genetic variants associated with ARHL are becoming available, through the analysis publicly available bioresources and electronic health records. These findings along with immunohistochemistry and mouse models of HL look set to help disentangle the genetic architecture of ARHL, and highlight the need for standardization of phenotyping methods to facilitate data sharing and collaboration across research networks.